2018
DOI: 10.24018/ejeng.2018.3.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Burnishing Operation for Corrosion Resistance Improvement of AISI 1017 Carbon Steel

Abstract: This research deal with investigation the influence of burnishing operation on the corrosion resistance of low carbon steel. The burnishing operation involve pressing a hard roller made from stainless steel on the surface of the rotatory shaft, this operation leads to the formation of a plastic deformation on the surface of the steel. Burnishing feed and burnishing speed were the variables which are used for this study. The first group involve hold burnishing speed on 125rpm with variable feeds of 0.6, 0.9, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…While some authors have reported that slide burnishing provides several benefits as improving corrosion which can be attributed roughness, grain size, etc. 13,20,21,24,26,27 The above results suggest that burnishing process applied over zinc coating does not show a significative variation on its corrosion resistance. Zinc is known for its high resistance to corrosion thanks to the formation of a protective layer of zinc oxide on its surface.…”
Section: Corrosion Test and X-ray Diffraction Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…While some authors have reported that slide burnishing provides several benefits as improving corrosion which can be attributed roughness, grain size, etc. 13,20,21,24,26,27 The above results suggest that burnishing process applied over zinc coating does not show a significative variation on its corrosion resistance. Zinc is known for its high resistance to corrosion thanks to the formation of a protective layer of zinc oxide on its surface.…”
Section: Corrosion Test and X-ray Diffraction Analysismentioning
confidence: 77%
“…Similar to the afore mentioned research, other studies demonstrate that the use of the appropriate burnishing parameters improves the corrosion resistance of different types of metallic materials, such as: A53 steel, X5XrNi 18-10 stainless steel, X6CrNiMoTi17-12-2 stainless steel, AZ31B Mg alloy, AISI 1017 carbon steel, 2024 aluminum alloy, and Mg-Al-Zn alloy. [21][22][23][24][25][26][27] Literature shows that the improvement in corrosion resistance is mainly attributed to the enhancement in surface roughness, grain refinement, strongly basaltexture grain orientation, and the introduction of compressive residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have studied the effect of burnishing on corrosion, including roughness, grain size, etc. [9][10][11][12][13][14], and these studies clearly indicate a change in the corrosion potential, this aspect is not or partially addressed in their results and discussions. Consequently, many authors attribute the alteration in corrosion potential mainly to roughness.…”
Section: Introductionmentioning
confidence: 89%